Sliding mode control of a PMSM railway traction drive fed by multi-level inverter - Vo Thanh Ha; Vo Quang Vinh (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
This work offers the sliding mode control (SMC) based control scheme for a railway traction transmission system fed by a five-level T-type inverter. This nonlinear control approach is created for the speed and torque loop control of the permanent magnet synchronous motor (PMSM) railway traction drive system supplied by a multi-level inverter. The article also includes a mathematical model of a PMSM motor and torque load to design controllers. The paper expressed the vector voltage modulation design incorporating a five-level T-Type inverter. The research proposes a control scheme for the railway traction drive system that enhances transmission quality by lowering the torque ripper and stator current harmonic distortion and extending converter life. Through MATLAB simulation, the study findings are validated.